(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
The aim of this paper is to point out various arguments which question ambiance as a common ground of everyday urban experience. Such a project involves four major points. First, we have to move beyond the exclusive practical aspects of everyday life and bring the sensory to the forefront. Under such conditions, sensory cultures emerge where feeling and acting come together. Second, we must put common experience into perspectiveby initiating a dual dynamics of socialising the sensory and sensitising social life. Ambiances involve a complex web comprised of an ‘existential’ dimension (empathy with the ambient world), a ‘contextual’ dimension (degree of presence in the situation), and an ‘interactional’ dimension (forms of sociability expressed in the tonality). Third, we have to initiate a political ecology of ambiances in order to better understand how ambiances deal with fundamental design and planning issues. Far from being neutral, the notion of ambiance appears to be bound up with the socio-aesthetic strategies underpinning changes to the sensory urban environment of the future. Fourth, we have to question what in situ experience is all about. Three major research pointers enable to address this issue: the embodiment of situated experiences, the porous nature of sensory spaces, and the sensory efficiency of the build environment. Ambiances sensitize urban design as well as social lifeforms.